Perbandingan Kinerja Algoritma C4.5 dan Naive Bayes Untuk Klasifikasi Penerima Beasiswa Studi Kasus di SMKS 2 Adi Luhur - Susanti, Lia; ., Khoirunnisa (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 4 (2024): JELIKU Volume 12 No 4, May 2024, 2024)
In advancing the Nation and State, a smart generation is needed. One of the most important factors is education, but many students who have great abilities and potential cannot continue school because they are not financially capable but there are also many able-bodied students who get scholarships. In the educational environment, especially schools, there should be some rules or classification in determining students who receive scholarships Therefore, in this study, a comparison of the C4.5 and Naïve Bayes algorithms was applied to the data of students who received scholarships. This study aims to find a pattern that can determine the award of scholarships with predetermined criteria, in the selection of prospective scholarship recipients at SMKS 2 Adi Luhur  using the Naive Bayes Algorithm and the C 4.5 Algorithm. The data will be tested using k-fold cross validation (k=10). From the comparison results, the results of the Naïve Bayes accuracy are higher than the C 4.5 Algorithm. The results obtained from the comparison of the two algorithms are the Naïve Bayes algorithm has an accuracy rate of   94.52% and the C4.5 algorithm has an accuracy rate of   92.52%.   Keywords : Scholarship, C4.5 Algorithm, Naïve Bayes, K-Fold Cross Validation, Classification